2020
DOI: 10.1186/s40537-020-00293-x
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian hierarchical analyses for entrepreneurial intention of students

Abstract: In recent years, entrepreneurship has become an important issue due to national economic development and the contribution of society. Data with a hierarchical structure received more attention and occur frequently in social science, public health and epidemiological researches. In such research, binary outcomes are common. Multilevel logistic regression models allow one to account for the clustering of subjects within clusters of higher-level units when estimating the effect of subject and cluster characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
(35 reference statements)
1
6
0
2
Order By: Relevance
“…This is because those two indicators demonstrate commitment and intention to become an entrepreneur, meaning they are ready to do anything in order to achieve their goal. The entrepreneurial intention among undergraduate students can be created through entrepreneurial education and training (Ayalew, 2020). Therefore, these five indicators should be incorporated in the curriculum of entrepreneurial education.…”
Section: Discussionmentioning
confidence: 99%
“…This is because those two indicators demonstrate commitment and intention to become an entrepreneur, meaning they are ready to do anything in order to achieve their goal. The entrepreneurial intention among undergraduate students can be created through entrepreneurial education and training (Ayalew, 2020). Therefore, these five indicators should be incorporated in the curriculum of entrepreneurial education.…”
Section: Discussionmentioning
confidence: 99%
“…Further-more, Botha et al (2007) found that the special women entrepreneurial programme (WEP) was effective and positively influenced business start-up and venture creation among women in South Africa. Several authors have shown other factors as influencing entrepreneurial propensity among youths to include: entrepreneurial education (Hahn et al, 2020;Ayalew, 2020), supportive environment (Walter & Block, 2016), and parents' entrepreneurial role (Liñán & Fayolle, 2015;Olofinyehun, Adelowo & Egbetokun, 2018;Hopp et al, 2019;Moussa and Kerkeni, 2021). Among the Hungarian students, Gubik (2021) found that positive entrepreneurial attitudes and better knowledge about entrepreneurship process has the chance to positively influence them towards entrepreneurship career.…”
Section: Table 1 Some Major Personal Entrepreneurial Characteristics Authorsmentioning
confidence: 99%
“…e arrival of the big data era provides college students with such data leasing, data analysis, decision-making outsourcing, data trading, and other entrepreneurial directions. In the era of big data, the huge amount of information has a significant impact on the decisionmaking and development of every enterprise and no enterprise can stay out of the matter [7]. Big data can promote college students' understanding of future demand development trends, and it is the opportunity for college students to choose the direction of entrepreneurship, which enhances the correctness and guarantee of entrepreneurial path selection [8].…”
Section: Introductionmentioning
confidence: 99%